The Role of Psychological Stress in Psoriasis: A Narrative Literature Review - Winda Wijayanti; Annisa Fildza Hashfi; Irene Ardiani Pramudya Wardhani; Muhammad Eko Irawanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Psoriasis is a chronic, persistent skin disease characterized by characteristic lesions in the form of well-defined erythematous patches covered by thick white, shiny scales resembling wax droplets. Psoriasis has a psychological, social, and emotional impact. Psychological stress has also been shown to influence the disease and course of psoriasis. Therapy in psoriasis patients with psychological stress can be given pharmacologically and psychologically. Patients with moderate to severe psoriasis using the Goeckerman regimen for psoriasis showed significant improvements in anxiety and depression scores. Psychological therapies such as relaxation therapy and meditation are able to control the emotions that trigger stress and reduce the appearance and severity of psoriasis. This literature review aims to describe the impact of psychological stress on psoriasis patients so as to increase awareness to detect psychological stress and provide appropriate treatment.